Influence and Impact of TikTok During the Pandemic to the Selected Young Adults in Barangay Holy Spirit, Quezon City: Towards A Guide: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research was conducted to assess the influence and impact of TikTok during the pandemic on the selected young adults in Barangay Holy Spirit Quezon City. It would be helpful to identify and analyze the advantages and disadvantages that TikTok brings to young adults to develop a guideline to help them minimize the use of TikTok. The researchers used survey questionnaires to collect data personally distributed to the young adults in Barangay Holy Spirit Quezon City. The descriptive statistics formula was utilized to interpret and determine if TikTok significantly influences and impacts family, friends, behaviour, lifestyle, academic performance, psychological health and physical health. Moreover, the mean, weighted mean, frequency, and percentage were used to gauge the rank and average of the variables and respondents’ responses, respectively. Corollary, with the help of the above-cited instruments, methodology, and statistical treatment, it was concluded that there was a significant influence and impact of TikTok on young adults.